2020
DOI: 10.1155/2020/6538156
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Antiulcerogenic Activity of Li‐Zhong Decoction on Duodenal Ulcers Induced by Indomethacin in Rats: Involvement of TLR‐2/MyD88 Signaling Pathway

Abstract: Background. Administration of nonsteroidal anti-inflammatory drugs (NSAIDs) often causes small intestinal ulcers in patients, but few effective drugs are currently available to manage such serious adverse events of NSAIDs. Li-Zhong decoction (LZD), a well-known traditional Chinese medicine (TCM) formula, is commonly prescribed for treatment of gastrointestinal diseases. The present study aimed to investigate the anti-ulcerogenic activity of LZD on indomethacin- (IND-) induced duodenal ulcer in rats. Mechanisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Morphometric data revealed a significant increase in inflammation grading score, crypts depth and muscle layer thickness when compared with the control group. Similar results were obtained by Song et al, (2020) and Yan et al, (2020) who reported the indomethacin-induced histopathological alterations within duodenal and colonic tissues. Song et al (2020) reported that severe macroscopic and microscopic destructions in the indomethacin treated rats were observed in duodenal tissues which revealed hemorrhagic necrosis, inflammatory infiltration, deformation of duodenal glands, deep ulcerations, submucosal edema , villus destruction, and crypt abscess.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Morphometric data revealed a significant increase in inflammation grading score, crypts depth and muscle layer thickness when compared with the control group. Similar results were obtained by Song et al, (2020) and Yan et al, (2020) who reported the indomethacin-induced histopathological alterations within duodenal and colonic tissues. Song et al (2020) reported that severe macroscopic and microscopic destructions in the indomethacin treated rats were observed in duodenal tissues which revealed hemorrhagic necrosis, inflammatory infiltration, deformation of duodenal glands, deep ulcerations, submucosal edema , villus destruction, and crypt abscess.…”
Section: Discussionsupporting
confidence: 89%
“…These results were found to be in an agreement with many authors. Katary and Salahuddin (2017) and Song et al (2020), reported that oral treatment by indomethacin-induced a significant elevation in proinflammatory cytokines TNF-α, IL-6 and MPO while it decreased anti-inflammatory cytokines IL-10, and evidently reduced intestinal mucosal PGE2 contents in albino rats. In our study, indomethacin-induced a significant elevation of serum CRP, these results agreed with those of Abd El-Kareem et al (2006) who observed that patients with ulcerative colitis showed elevated Serum C-reactive protein (CRP) than normal group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant drawback of the extensive use of a common non-steroidal anti-inflammatory drug (Indomethacin) is the development of gastric ulcers ( Song et al, 2020b ). Multiple studies consider IND-induced gastric ulcers in rats as a standard model to investigate the underlying pathophysiological and pharmacological mechanisms ( Liu et al, 2015 ; Gomaa et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%